Exploring a faith-based approach to puberty education in Tanzania - Teizazu, Hawi; Gruer, Caitlin; Mandara, Elisia; Sommer, Marni (Frontiers in Reproductive Health, 2023)
Background Many adolescents in Tanzania do not receive timely and comprehensive puberty education. This study explored faith-based organizations a site for puberty education. Two puberty books, each developed through participatory research with Tanzanian adolescents and stakeholders, were promoted to 177 Christian denomination churches in Dar es Salaam, Tanzania to understand the factors that faith leaders considered in their decision to purchase puberty books, or share information about the intervention to their peers and congregants. Methods Data collection included routine monitoring via weekly reports and ethnographic observation. Data were analyzed using the Ecological Framework for Health Promotion to capture how individual, interpersonal, and institutional factors influenced leaders' decisions to purchase or promote puberty books. Results At the individual level, leaders cited their personal experiences in their support for the intervention, but leaders' time and confidence in their ability to effectively promote books to others were barriers to participation. Interpersonally, the diffusion of information between church leaders, particularly when information came from well-known or respected leaders, emerged as an important factor in leaders' willingness to promote books. At the institutional level, leaders' decisions were impacted by resources, institutional culture, and institutional hierarchy. Importantly, twelve churches in the sample purchased books. Limited financial resources and the need to receive approval from denominational leaders were discussed by leaders as barriers to purchasing books. Conclusions Despite research showing high religiosity in Tanzania, the role of religious institutions in providing puberty education has remained unexplored. Our results inform future research and practice by providing an articulation of the socioecological factors that played a role in faith leaders' decisions related to puberty education interventions in Tanzania.